Benzodiazepine receptor agonists significantly increase the risk of pneumonia - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
The results of a new study have shown that popular treatments for anxiety and insomnia have a dangerous side effect.